Moral intuitions, punishment ideology, and judicial sentencing - Silver, Jason R. (Journal of crime and justice, 2024)
Considerable research examines discretion in judicial sentencing. However, little is known about the role of moral values or ideological beliefs in judicial sentencing decisions. The current study draws on insights from moral psychology to propose a model of judicial decision-making in which moral intuitions may inform sentencing both directly and indirectly via ideological beliefs about punishment (including general punitiveness and concern for offenders). We test this model using a statewide survey of Pennsylvania Common Pleas Criminal Court judges (N = 132), which included hypothetical sentencing vignettes. Results indicate that although moral intuitions were related to punishment ideology, moral intuitions were largely unrelated to judicial sentencing decisions, with a few exceptions. We interpret the results as suggesting that while moral and ideological preferences may be relevant under some circumstances, the role of morality in judicial decision-making may be constrained by legal or organizational factors.